Incorporating a piperidinyl group in the fluorophore extends the fluorescence lifetime of click-derived cyclam-naphthalimide conjugates. - Mingfeng Yu; Sandra Ast; Qun Yu; Anthony T S Lo; Roman Flehr; Matthew H Todd; Peter J Rutledge (PLoS ONE, 2014)
Ligands incorporating a tetraazamacrocycle receptor, a 'click'-derived triazole and a 1,8-naphthalimide fluorophore have proven utility as probes for metal ions. Three new cyclam-based molecular probes are reported, in which a piperidinyl group has been introduced at the 4-position of the naphthalimide fluorophore. These compounds have been synthesized using the copper(I)-catalyzed azide-alkyne Huisgen cycloaddition and their photophysical properties studied in detail. The alkylamino group induces the expected red-shift in absorption and emission spectra relative to the simple naphthalimide derivatives and gives rise to extended fluorescence lifetimes in aqueous buffer. The photophysical properties of these systems are shown to be highly solvent-dependent. Screening the fluorescence responses of the new conjugates to a wide variety of metal ions reveals significant and selective fluorescence quenching in the presence of copper(II), yet no fluorescence enhancement with zinc(II) as observed previously for the simple naphthalimide derivatives. Reasons for this different behaviour are proposed. Cytotoxicity testing shows that these new cyclam-triazole-dye conjugates display little or no toxicity against either DLD-1 colon carcinoma cells or MDA-MB-231 breast carcinoma cells, suggesting a potential role for these and related systems in biological sensing applications.